Sexual Behavior of Javan Langur (Trachypithecus auratus) in Taman Safari Indonesia Ex-situ Conservation Facility (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2019)
Trachypithecus auratus is one of the vulnerable primate species that is declining in number due to illegal hunting and forest degradation. The efforts to increase population can be through ex-situ conservation program that are specific to reproduction. To date, little is known about the reproduction of this species, particularly in the aspect of sexual behavior. The aim of this research was to analyze the sexual behavior of T. auratus at the Taman Safari Indonesia ex-situ conservation facility. This research conducted on five adult individuals from a group of consisting of one male and four females. The group of T. auratus were observed for five months from September 2018 until January 2019. The method used focal animal sampling with BORIS (Behavioral Observation Research Interactive Software). The results showed that the females performed pre-copulation (courtship) behavior such as head shaking (28.90%), hindquarter present (17.33%), raising a forelimb (11.66%), and the male performed pre-copulation (courtship) behavior such as genital inspection (68.46%). Copulation lasts for 60 seconds, starting with male mounting and thrusting as many as 40 seconds and ejaculation which is thought to occur for 20 seconds. At the end of the copulation sequence, a pair of T. auratus showed grooming and foraging together. The conclusion of this research was T. auratus has parameters of sexual behavior with copulation that lasts for 60 seconds and head shaking was sexual behavior that can be used as an signal for mating. This research are expected to be used as basic reproductive biology data to support the breeding and conservation program of T. auratus species.
Keywords: Copulation; reproduction; sexual behavior; Trachypithecus auratus